1996
DOI: 10.1177/089198879600900305
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Parkinsonism Associated with Dysphagia and Aspiration: A Brief Report

Abstract: Idiopathic Parkinsonism is a well-recognized cause of dysphagia and resultant aspiration. Symptoms and signs attributable to dopaminergic underactivity after administration of antipsychotic medication are commonly seen in elderly patients. We report a case of a 74-year-old woman, without prior symptoms of Parkinsonism or dysphagia, who presented with the temporal association of both after administration of trifluoperazine hydrochloride. Dysphagia is a potentially life-threatening complication of drug-induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…With an age range of 35-79 years, demographic characteristics outlined in Table 1 suggest that bradykinetic EPSrelated dysphagia may occur in patients of all ages. Medium-to high-potency conventional antipsychotics are commonly implicated (8 of 11 cases [15,16,[18][19][20][21]23] and present case), although atypical neuroleptics have also caused dysphagia (3 cases [17,22]). Dysphagia may occur together with other parkinsonian features (4 cases) or may be the only prominent manifestation of EPS (6 cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an age range of 35-79 years, demographic characteristics outlined in Table 1 suggest that bradykinetic EPSrelated dysphagia may occur in patients of all ages. Medium-to high-potency conventional antipsychotics are commonly implicated (8 of 11 cases [15,16,[18][19][20][21]23] and present case), although atypical neuroleptics have also caused dysphagia (3 cases [17,22]). Dysphagia may occur together with other parkinsonian features (4 cases) or may be the only prominent manifestation of EPS (6 cases).…”
Section: Discussionmentioning
confidence: 99%
“…There have been some interesting observations in a number of case reports [15][16][17][18][19][20][21][22][23]. With an age range of 35-79 years, demographic characteristics outlined in Table 1 suggest that bradykinetic EPSrelated dysphagia may occur in patients of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy defects in HD resulted from the failure to sequester protein aggregates, lipid stores and dysfunctional mitochondria, not from a defect in fusion of autophagic vacuoles with lysosomes or reduced proteolytic activity within autophagolysosomes [114]. On the other hand, there are some studies demonstrating that modulation of autophagy would be a promising therapeutic strategy in HD [100,115]. Among these reports, Ravikumar et al [116] reported that rapamycin reduced the levels of aggregate-prone proteins and cell death associated with polyglutamine and polyalanine expansions in PC12 cells.…”
Section: Role Of Induced Autophagy In Hdmentioning
confidence: 98%
“…Höllerhage et al [98] found that the phenothiazine neuroleptic trifluoperazine, an activator of autophagy, selectively reduced one particular a-synuclein species in human post-mitotic dopaminergic neurons. Chronic trifluoperazine was shown to induce Parkinsonism-like symptoms in humans and experimental animals [99,100]. Steele et al [101] found that latrepiridine stimulated degradation of a-synculein in differentiated SH-SY5Y neurons and mouse brain through increasing autophagic activity.…”
Section: Role Of Induced Autophagy In Pdmentioning
confidence: 98%
“…The half-life of haloperidol is approximately 21 hours, with peak plasma concentrations noted within 2 to 6 hours of dosing (enteral) or 20 minutes (intramuscular). Notable side effects of the drug can include hypotension that antagonizes adrenaline (especially in parenteral form), dose-dependent QTc prolongation leading to cardiac tachyarrhythmias such as torsades des pointes [68][69][70]-particularly among those with pre-existing cardiac disease and in those who receive a more than 35 mg cumulative dose-extrapyramidal symptoms [71], neuroleptic malignant syndrome [72], dysphoria [73], or laryngospasm [74]. Meanwhile, the atypical antipsychotics typically have half-lives of at least 20 hours, with the exception of ziprasidone (~ 7 hours).…”
Section: Drug Therapymentioning
confidence: 99%